Análisis de la promoción audiovisual sobre las construcciones de la época republicana del centro histórico del cantón Latacunga. - Tipanguano Astudillo, Alex Federico (2018)
The present project contextualizes different concepts of historians, related to the definition of Latcunga historical center and its audiovisual promotion on local television. The development of the work begins with the definition of Latacunga historical center: its elements and problems that deal this patrimonial space, also allows to identify the elements of cultural representative value to city and its relation with the Inhabitants of this place. There is some problems for instance ignorance and lack of attention of the society, because of Latacunga historical center is an object of destruction, in spite of the existence of norms and laws in forcé. There has not been following out the necessary to the People who infringe and proceed to the destruction of several elements. The diversity of problems also covers the relations between the historical center and the media television of the private sector of the locality, that’s why the lack of spaces dedicated to the diffusion of cultural patrimony of the city. More over, the deficiency to promote intercultural spaces in spite of the requirement of the LOC (Organic Law of communication), where it indicate that. It must inforance with 5% of the percentage of the programming to the interculturality of country. In the methodological part to diagnose the different problems and fulfil the purpose of the work, it based on the qualitative method and through the description of data obtained through the application of interviews as an instrument selected for the fulfillment of the proposed objectives. The description of results starts according to the order marked on the selection of the specific objectives, which starting from the definition of the historic center, elements and problems present in this space. Then the local representative buildings are narrated based on the perspective of the interviewed historians, On top of that also there is done an analysis of the local television with regard to the opening of segments or spaces dedicated to the diffusion of the historical center. Finally; it comprises a series of aspects related to the strengthening of the dissemination of the property of historic center of Latacunga on local television, this according to the criterion of the historians or people who are experts in the subject of cultural heritage.